Prevalence and determinants of underweight, overweight, and obesity among reproductive-aged Bangladeshi women: Evidence from Bangladesh Demographic and Health Survey 2022 - Ashim Kumar Nandi; Kh Shafiur Rahaman; Navira Chandio; Amit Arora (PLoS ONE, 2026)
Over the past two decades, underweight, overweight, and obesity have increased in Bangladesh, becoming a major public health concern. This study investigated the current prevalence and examined the determinants of underweight, overweight, and obesity among reproductive-aged Bangladeshi women. Using data from a weighted sample of 9,213 women in the 2022 Bangladesh Demographic and Health Survey, we applied multinomial logistic regression to identify factors independently associated with being underweight, overweight, and obese. Among 9,213 reproductive-aged women, the prevalence of underweight, overweight, and obesity was 10.0%, 18.9%, and 36.5%, respectively. Multivariable analysis identified older age as the strongest predictor of overweight and obesity: women aged 35–49 years had nearly double the risk of overweight (ARRR = 2.01; 95% CI: 1.62–2.50) and more than triple the risk of obesity (ARRR = 3.56; 95% CI: 2.90–4.38) compared to those aged 15–24 years. Other significant factors included higher wealth status (ARRR = 1.94; 95% CI: 1.66–2.26 for obesity among wealthy households), media exposure (reading magazines: ARRR = 1.46; 95% CI: 1.14–1.87, watching television: ARRR = 1.28; 95% CI: 1.13–1.46), and parity (ARRR = 1.58; 95% CI: 1.23–2.02 for obesity among women with 1–4 children). Breastfeeding and agricultural/manual work protected against obesity. We also found that currently breastfeeding women (ARRR = 1.40; 95% CI: 1.13–1.72) and women who lived in Sylhet division (ARRR = 1.55; 95% CI: 1.13–2.12) were more likely to be underweight, while women with secondary or higher education, wealthier women, women aged 25 or higher, and women with 1–4 children were less likely to be underweight. Overall, a higher burden of underweight, overweight, and obesity exists in the sample. These findings emphasise the need for age- and context-specific interventions, such as promoting active lifestyles, regulating food environments, and incorporating nutrition education into maternal health programs, to combat rising obesity while addressing persistent underweight.